2020
DOI: 10.1111/dth.14143
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐rich plasma for androgenetic alopecia: Efficacy differences between men and women

Abstract: Platelet-rich plasma (PRP) may be effective for treating androgenetic alopecia (AGA); albeit, its efficacy in men and women is still debated. We conducted meta-analyses to determine PRP efficacy in men and women separately. Studies were identified after systematically searching for trials that investigated PRP monotherapy for AGA in men and women separately. We included trials that studied PRP injections on hair density and/or hair diameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 45 publications
(167 reference statements)
4
24
1
5
Order By: Relevance
“…18 of 24 xenografts), while the xenografts of two patients were unresponsive to autologous PRP treatment. This corresponds very well to the highly variable outcome of PRP treatment during AGA management seen in clinical practice 2,5,6 . Thus, the current humanized AGA mouse model may provide an excellent preclinical research tool for elucidating the as yet entirely unknown molecular basis of what distinguishes PRP responders from nonresponders.…”
Section: Figuresupporting
confidence: 56%
“…18 of 24 xenografts), while the xenografts of two patients were unresponsive to autologous PRP treatment. This corresponds very well to the highly variable outcome of PRP treatment during AGA management seen in clinical practice 2,5,6 . Thus, the current humanized AGA mouse model may provide an excellent preclinical research tool for elucidating the as yet entirely unknown molecular basis of what distinguishes PRP responders from nonresponders.…”
Section: Figuresupporting
confidence: 56%
“…Differences in the treatment efficacy for AGA with PRP between men and women was discovered by a meta-analysis study, which revealed that PRP significantly increased both hair density (N = 250, MD = 25.83, 95% CI: 15.48–36.17, P < 0.00001) and hair diameter (N = 123, MD = 6.66, 95% CI: 2.37–10.95, P = 0.002) in men while significantly increased hair diameter (N = 95, MD = 31.22, 95% CI: 7.52–54.91, P = 0.01), but did not increase hair density (N = 92, MD = 43.54, 95% CI: −1.35–88.43, P = 0.06) in women. 53 However, PRP effectiveness in the treatment of AGA is influenced by gender is still controversial because of the differences in several reports listed, many of the analyzed studies were non-randomized, uncontrolled, and had small sample size.…”
Section: Use Of Platelet Rich Plasma In Hair Disordersmentioning
confidence: 99%
“…Patients may be more willing to try over-the-counter products prior to seeing a specialist for treatment recommendations. We assumed patients who continued therapy through more than one cycle were more likely to continue if they had improvement on treatment and 98% would continue treatment if they were compliant and motivated through subsequent cycles [ 1 , 4 ]. For men who had no change/worse responses, we assumed 50% would continue treatment if they were compliant and motivated through subsequent cycles [ 1 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…We assumed patients who continued therapy through more than one cycle were more likely to continue if they had improvement on treatment and 98% would continue treatment if they were compliant and motivated through subsequent cycles [ 1 , 4 ]. For men who had no change/worse responses, we assumed 50% would continue treatment if they were compliant and motivated through subsequent cycles [ 1 , 4 ]. Over subsequent cycles, men with no change/worse responses would eventually discontinue treatments as time progressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation